(untitled) (Research Nepal Journal of Development Studies, 2019)
Old-age homes are Sanyas Ashrams in Vedic philosophy. Sanyas Ashram is the preparation of death and it teaches the art of death. It is the university of art of death of old and experienced people who can share the knowledge and experiences of their lifetime achievements. The main objective of the study is to examine the socio economic and cultural status of old-age people living in Deveghat pilgrimage areas. It is a mini ethnography study based on field visit observation, focus group discussion and unstructured interview. I conclude that the old-age homes of Devghat are normal in-terms of the lifestyle of the elderly living there, their happiness level and the facility provided to them. Lastly the major reasons behind them coming to the old-age home was rather found to be in a mixed bag form as some came there due to the social reasons and economic reasons and some due to their faith in god and in belief of getting peace after death. But it has long way to go to make like a heaven type of Sanyas Ashram. At least it must be like a Vrindavan with entire worldly facilities of learning and sharing of knowledge production university.